(untitled) (Journal of the College of Basic Education, 2022)
It is obvious that the theatrical performance is a set of elements that must be available to create successive scenes that the audience enjoys watching. Its first thread is the theatrical text, which turns from words written on paper into live events embodied on stage.As for the theatrical decoration, it is one of the pillars of the theatrical show and is one of the important elements in conveying the message of the text to the viewer (5, p. 331). The visual image in the theater is one of the first indications through which a distinction is made between one location and another, and this image is complemented by the lighting and the actor.When designing an interior scene on the stage, it is possible to seek the help of interior designs taken from their natural locations, in their various shapes and functions, by the decorator. And placed on the stage to draw a picture of the desired theatrical scene. It is usual for the interior design to have been designed primarily for a function and a specific aesthetic goal, as the components of the interior space serve the occupant of the place, which entails the need to study various sciences such as human and industrial engineering, psychological sciences, etc.The problem of this research lies when this design is transferred from reality to the stage, so does the function of the design and its aesthetic goals remain the same? If there are differences in function, content and objectives, what are those differences? How can the designer employ the same internal space on stage with a successful transfer of what has been designed for purposes different from the purposes and objectives of the theatrical show?